Observing Silence - Paul Armstrong (Adult Education Research Conference, 2007)
The interpretation of silence depends on meanings that are negotiated in a particular social and cultural location, or place and space. Silence is an under-theorized and under-researched aspect of adult learning. The complexities and salience of silence in teaching and learning, methodological issues around observing and researching silence are explored.